2005
DOI: 10.1097/01.sap.0000183790.50079.e2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduction Mammoplasty on Upper-Limb Nerve Conduction Across the Thoracic Outlet in Women With Macromastia

Abstract: Consecutive patients undergoing BBR were randomized into 2 groups, depending on time of surgery. None had any prior neurologic disorder. Each patient had a comprehensive neurologic assessment and 2 electrodiagnostic neurophysiologic tests. Group 1 had 2 tests, one before surgery and a second 3 months postsurgery, while Group 2 had 2 sets of tests, one initially and a second test 4 months later (control). The outcome measures include somatosensory evoked potential (SSEP) (median and ulnar), F-wave median and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In a large cohort of 151 women undergoing BBR for macromastia, Pernia et al5 reported increased prevalence of clinically diagnosed CTS at 19.9%, as compared with 3% in women in general 15. Iwuagwu et al3, 6 and Guerra et al7 have independently confirmed the increased prevalence of CTS in women undergoing BBR, based on EDx criteria.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In a large cohort of 151 women undergoing BBR for macromastia, Pernia et al5 reported increased prevalence of clinically diagnosed CTS at 19.9%, as compared with 3% in women in general 15. Iwuagwu et al3, 6 and Guerra et al7 have independently confirmed the increased prevalence of CTS in women undergoing BBR, based on EDx criteria.…”
Section: Discussionmentioning
confidence: 89%
“…The prevalence of CTS based on EDx criteria in our select group was 33.3%. Although the clinical features of CTS and proximal T1 denervation overlap, increased prevalence of CTS in women undergoing BBR has been reported in separate studies based on clinical and EDx criteria 3, 5–7. In a large cohort of 151 women undergoing BBR for macromastia, Pernia et al5 reported increased prevalence of clinically diagnosed CTS at 19.9%, as compared with 3% in women in general 15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the clinical features of CTS and proximal T1 denervation overlap, increased prevalence of CTS in women undergoing BBR has been reported in separate studies based on clinical and EDx criteria. 3,[5][6][7] In a large cohort of 151 women undergoing BBR for macromastia, Pernia et al 5 reported increased prevalence of clinically diagnosed CTS at 19.9%, as compared with 3% in women in general. 15 Iwuagwu et al 3,6 and Guerra et al 7 have independently confirmed the increased prevalence of CTS in women undergoing BBR, based on EDx criteria.…”
Section: Predominant Involvement Of the Apb Muscle And The Macn Snap mentioning
confidence: 99%